Mitigating pedagogical challenges through culture-based approach: Javanese language learning in rural Yogyakarta, Indonesia - Harwati, Lusia Neti; Sathian, Mala Rajo (Indonesian Journal of Applied Linguistics, 2024)
Javanese is a vernacular language used in the Special Region of Yogyakarta, Indonesia. The dominance of the national language, Bahasa Indonesia, in the country’s curriculum is commonly presumed as a threat to the survival of Javanese. Thus, the Yogyakarta administrators have attempted to preserve Javanese through the education sector, strengthened through provincial regulations that focus on providing quality education based on Javanese cultural values. This paper examines students’ perceptions of the importance and challenges of Javanese learning based on data obtained from sixth grade students and 4 Javanese language teachers from two schools in Yogyakarta. The findings through questionnaire, classroom observation, and focus group discussion reveal that both teachers and students are mainly challenged in learning Javanese owing to the complexity of Javanese speech levels and the obligation to use students’ worksheet with specific learning targets in each semester. Despite the challenges, these aspects are viewed as necessary components of learning process and fundamental in fostering competence in Javanese language that forms an integral part of the people’s identity. Creative ways to learn Javanese through culture-based approach is essential. The position of the vernacular in Yogyakarta viewed from the intersectional lens of language nationalism and globalization indicate that Javanese is threatened less due to the predominance of Bahasa Indonesia. Rather, its complex learning process in view of the rapid technological and globalized ways of learning poses a bigger challenge.